Comparison of Postoperative Recovery rates in Cervical Spondylotic Myelopathy Patients Based on Spinal Cord Signal Changes (Bangladesh Journal of Neurosurgery, 2026)
Background: Cervical spondylotic myelopathy is associated with pathological changes in the spinal cord  which is often reflected by the change in the signal intensity of the spinal cord observed on Magnetic  Resonance Imaging (MRI). The prognostic significance of this signal intensity changes in preoperative  patients remains controversial.  Objectives: To compare the recovery rate on the 30th postoperative day, between the cervical spondylotic  myelopathy patients with and without preoperative hyperintensity changes in the cervical cord in MRI T2  weighted images.  Materials and Methods: The type of the study was surgical prospective study. The place of the study was  Bangladesh Medical University, Dhaka. The study population consisted of cervical spondylotic myelopathy  patients of all ages and both sexes. Only the patients with a single level disc prolapse were included. All  patients underwent anterior cervical discectomy and fusion (ACDF) with titanium cage. Purposive sampling  was used as the sampling technique. Sample size was 32. Interviewer administered questionnaires and  data collection sheets were used as data collection tools. There was no loss to follow up patients.  Statistical analysis: Data were processed and analyzed by using computer software SPSS (Statistical  Package for Social Sciences) version 26. Unpaired t test, Fisher’s exact test and Mann-Whitney U test were  done for data analysis. Statistical significance was set at p-value